Welcome :: Homework Help and Answers :: Mathskey.com
Welcome to Mathskey.com Question & Answers Community. Ask any math/science homework question and receive answers from other members of the community.

13,433 questions

17,804 answers

1,438 comments

47,281 users

Differentiate root x^2+1/(x-9)^2?

+1 vote
With full working out plz ASAP thanks
asked Jan 30, 2013 in CALCULUS by angel12 Scholar

1 Answer

+1 vote

= √(x2 + 1) / (x - 9)2

Quotient rule: (d/dx)[g(x)/h(x)] =[ h(x) g'(x) - g(x) h'(x)] / h(x)²

={ (x - 9)2 √(x2 + 1)' - √(x2 + 1)[(x - 9)2]'} / [(x - 9)2]2

General derivative formulas: (d/dx)(√x) = 1/(2√x) and (d/dx)(an) = nan-1

= { (x - 9)2 [1/2√(x2 + 1)](2x) - √(x2 + 1)[2(x - 9)](1)} / [(x - 9)2]2

= { (x - 9)2 [1/√(x2 + 1)](x) - √(x2 + 1)[2(x - 9)]} / [(x - 9)2]2

= {[ x(x - 9)2 / √(x2 + 1)] - 2(x - 9)√(x2 + 1) } / [(x - 9)2]2

Take out common factors.

= (x-9){[ x(x - 9) / √(x2 + 1)] - 2√(x2 + 1)} / (x - 9)4

= {[ x(x - 9) / √(x2 + 1)] - 2√(x2 + 1)} / (x - 9)3

Rewrite the expression with common denominator.

= 1/√(x2 + 1){[ x(x - 9) - 2 √(x2 + 1)√(x2 + 1)} / (x - 9)3

= 1/√(x2 + 1){( x2 - 9x) - 2 (x2 + 1)} / (x - 9)3

={( x2 - 9x) - 2 (x2 + 1)} / √(x2 + 1)(x - 9)3

= (x2 - 9x - 2x2 - 2) / [√(x2 + 1)(x - 9)3]

= (- x2 - 9x - 2) / [(x - 9)3√(x2 + 1)]

answered Jan 31, 2013 by richardson Scholar

Related questions

asked Oct 11, 2014 in CALCULUS by anonymous
asked Oct 4, 2014 in CALCULUS by anonymous
asked Jul 22, 2014 in CALCULUS by anonymous
asked Jul 10, 2014 in CALCULUS by anonymous
asked May 17, 2014 in CALCULUS by anonymous
...